2018
DOI: 10.1039/c8nr06418k
|View full text |Cite
|
Sign up to set email alerts
|

Solution-phase synthesized iron telluride nanostructures with controllable thermally triggered p-type to n-type transition

Abstract: We report the solution-phase synthesis of iron telluride with controllable reversible switching behavior between p- and n-type conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Moreover, since FeTe 2 monolayers are predicted to preserve a ferromagnetic state due to magnetocrystalline anisotropy arising from spin-orbit coupling, further magneto-optic experiments are of interest to test theoretical predictions. Two-dimensional materials with ferromagnetic ground states attract great interest as they are possible candidates for spintronic and memory devices but can also be valuable in fundamental science studies. Finally, since reproducible switching behavior without crystal structure changes has recently been reported in FeTe 2 nanostructures, it would be of interest to investigate the size dependence of switching properties in future devices made from FeTe 2 ultrathin crystals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since FeTe 2 monolayers are predicted to preserve a ferromagnetic state due to magnetocrystalline anisotropy arising from spin-orbit coupling, further magneto-optic experiments are of interest to test theoretical predictions. Two-dimensional materials with ferromagnetic ground states attract great interest as they are possible candidates for spintronic and memory devices but can also be valuable in fundamental science studies. Finally, since reproducible switching behavior without crystal structure changes has recently been reported in FeTe 2 nanostructures, it would be of interest to investigate the size dependence of switching properties in future devices made from FeTe 2 ultrathin crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional materials with ferromagnetic ground states attract great interest as they are possible candidates for spintronic and memory devices but can also be valuable in fundamental science studies. 35−37 Finally, since reproducible switching behavior without crystal structure changes has recently been reported in FeTe 2 nanostructures, 38 it would be of interest to investigate the size dependence of switching properties in future devices made from FeTe 2 ultrathin crystals.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It is experimentally observed that FeTe 2 crystal has an antiferromagnetic lowest energy phase with anisotropic behavior <∼80 K and a ferromagnetic (FM) state <30 K [10]. Additionally, FeTe 2 system exhibits bipolar conduction, which means that main carrier switches at a certain temperature, resulting in poor thermometric performance [12,13]. Moreover, An et al experimentally studied the impact of Ni doping on electrical and thermal properties of FeTe 2 , and found an increase in electrical conductivity with increasing temperature [14].…”
Section: Introductionmentioning
confidence: 99%